ANALYSIS OF STORM CATEGORY AND COALESCENCE ACTIVITY : RELATIONSHIP TO THE DAILY MEAN CATCHMENT RAINFALL (CASES CLOUD SEEDING OPERATIONAL IN LARONA AND CITARUM CATCHMENT AREA) - Haryanto, Untung; Harsanti, Dini; Goenawan, R. Djoko; Adithya, Krisna (BPPT, 2012)
Cloud seeding operational has been conducted in Indonesia. In this study, the two cases operational were analysis, ie Larona (2005) and Citarum Catchment Area (2011). The coalescence activity during operational were analysed using archives of NOAAGFS model sounding and it also used to determined storm category and ICA. For this purpose, the number parameters for moderate threshold range on Raob-55 software were reduced and modified with more suitable range for Indonesia region. Result indicated that in Larona Catchment Area, the most of the storm having category weak to moderate with mean of storm category 67% and 21% respectively, the mean ICA value was -5.7. Relative larger weight of Weak and Medium category of storm were shown in Citarum ie 72% for weak and 18%, with the mean of ICA was -2.7%. As consequences, proportion of Medium together with Strong category for Larona is larger than Citarum,resulting larger amount mean catchment rainfall for Larona (17.1mm) compare to the Citarum (5.2 mm). The coalescence actifity in cloud during operation was effective for booth of two area, but varies due to the varies of cloud base height temperature and potential buoyancy (PB). The mean of CCL temperature in Larona was 20.30C since PB was 3.80C. This study also found that mean 500mb temperature (T) and mean rising parcel (TP) in Larona catchments was more warmer comparing to the Citarum is -4.00C and -0.150C for Larona , and -5.30C and -1.50C for Citarum. Base of the result it has been concluded that ICA has inverse correlation to the mean daily catchments rainfall, since together of Medium and Strong Storm Category has positive correlation.Modifikasi awan sudah operasional. Pada studi ini dilakukan analisis dua kasus operasional , yaitu operasional di DAS (Daerah Aliran Sungai) Larona (2005) dan DAS Citarum (2011). Aktifitas koalesensi selama operasional dianalisis menggunakan arsip data sounding NOAA-GFS yang digunakan untuk menentukan ICA (Index Coalescence Activity ? indeks aktifitas koealesensi) dan Storm Category ? kategori awan hujan). Bagi keperluan ini banyaknya parameter dan rentang kategori moderat pada perangkat lunak Raob -55 di dikurangi dan dimodifikasi dengan yang paling sesuai dengan kondisi daerah di Indonesia. Hasil analisis menunjukkan sebagian besar awan hujan yang ada memiliki kategori weak hingga moderat ? yaitu 67% dan 21% di DAS Larona dengan rata-rata nilai ICA besarnya -5.7, sedangkan di DAS Citarum, nilai kategori ini lebih besar yaitu 72% dan 18% dengan nilai rata rata ICA adalah -2.7. Sebagai konsekuensinya adalah porsi awan hujan dengan kategori ini lebih banyak muncul di DAS Larona dibandingkan pada DAS Citarum dengan rata rata hujan masing masing 17.1mm di DAS Larona dan 5.2mm di DAS Citarum. Aktivitas koalesensi di kedua DAS ini sama-sama aktif, variasinya ditentukan oleh variasi ketinggian dasar awan konvektif (CCL) dan potensi daya apung awan (PB). Di DAS Larona CCL cukup hangat yaitu 20.30C , dengan nilai PB 3.80C. Pada sutudi ini juga di peroleh bahwa rata rata suhu dan suhu parsel paras 500mb pada DAS Larona lebih hangat (-4.00C dan -0.150C) dari pada di DAS Citarum (-5.30C dan -1.50C). Dari studi ini, disimpulkan bahwa ICA berkorelasi terbalik dengan curah hujan harian, dan berkorelasi positif dengan awan hujan berkategori ? sedang? dan ?kuat? secara bersama-sama.